Pendidikan Etika Dalam Kakawin Niti Sastra - I Putu Agus Aryatnaya Giri; Muliani, Ni Made; Girinata, I Made (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2025)
Kakawin Niti Sastra in the chanting of the Dharma Gita is often performed in various pesantian events in Bali, but it seems that it is not accompanied by an in-depth study of the values ​​of ethical education contained therein. Therefore, the study of ethical education in Kakawin Niti Sastra is very relevant if applied and realized in the current era of globalization. The results of the study show that many interesting things can be described when examining the values ​​of ethical education in Kakawin Niti Sastra which in this context discusses ethical education based on Hindu teachings, namely Tri Kaya Parisuddha. Holistically, this Hindu ethical teaching covers aspects of human work physically and spiritually. The process of thinking (manacika) becomes the beginning of a statement (wacika) or action (kayika) that occurs in humans. The definition of Tri Kaya Parisuddha means three purified actions. Tri Kaya Parisuddha as part of the teachings of ethical education in Hinduism will provide guidance and a path to peace and harmony in life in the world and the hereafter.